Life cycle environmental impacts of advanced wastewater treatment techniques for removal of pharmaceuticals and personal care products (PPCPs). (1st June 2018) - Zepon Tarpani, Raphael Ricardo; Azapagic, Adisa
Abstract: Pharmaceutical and personal care products (PPCPs) are of increasing interest because of their ecotoxicological properties and environmental impacts. Wastewater treatment plants (WWTPs) are the main pathway for their release into freshwaters due to the inefficiency of conventional WWTPs in removing many of these contaminants from effluents. Therefore, different advanced effluent treatment techniques have been proposed for their treatment. However, it is not known at present how effective these treatment methods are and whether on a life cycle basis they cause other environmental impacts which may outweigh the benefits of the treatment. In an effort to provide an insight into this question, this paper considers life cycle environmental impacts of the following advanced treatment techniques aimed at reducing freshwater ecotoxicity potential of PPCPs: granular activated carbon (GAC), nanofiltration (NF), solar photo-Fenton (SPF) and ozonation. The results suggest that on average NF has the lowest impacts for 13 out of 18 categories considered. GAC is the best alternative for five impacts, including metals and water depletion, but it has the highest marine eutrophication. SPF and ozonation are the least sustainable for eight impacts, including ecotoxicity and climate change. GAC and NF are also more efficient in treating heavy metals while avoiding generation of harmful by-products during the treatment, thus being more suitable for potable reuse of wastewater. However, releasing the effluent without advanced treatment to agricultural land achieves a much higher reduction of freshwater ecotoxicity than treating it by any of the advanced treatments and releasing to the environment. Therefore, the use of advanced effluent treatment for agricultural purposes is not recommended. Graphical abstract: Image 1 Highlights: Nanofiltration has the lowest life cycle impacts followed by granular activated carbon. Solar photo-Fenton (SPF) and ozonation are environmentally the least sustainable. SPF has higher life cycle freshwater ecotoxicity than untreated effluent. Use of advanced effluent treatment for agricultural purposes is not recommended.